The Structured Frame of Category Management for Optimization of Retail Business - Rashid, Md. Sanuwar (Indian Journal of Marketing, 2011)
Since the industrial revolution in the early 19th century, we have touched the milestone of modernism. And from early modernism to post modernity, industries have gradually moved towards consumers’ needs and wishes. Nowadays, consumers deserve to have things as per their wishes. It means that mass marketing is replaced by mass customization. To achieve the goal of mass customization, the supplier and retailer need to contribute their efforts to understand consumer needs. In this paradigm, Category management became the key player for changing the role of supplier and retailer. In 1990s, Wal-Mart successfully applied this new theory for bringing its supercenter format, which converted retailer’s general merchandise store into a full-line grocery store under a single roof. In the present paper, the author has shown how retailers and suppliers can adopt the category management business process to avail the full benefits from it.